The role of competitive advantage in the marketing performance of culinary MSMEs in Semarang Regency - Risma Lestari; Dewi Widyaningsih; Myra Andriana (Universitas Nusa Cendana, 2026)
This study aims to examine the effects of digital marketing, price penetration, product innovation, and competitor orientation on the marketing performance of culinary MSMEs in Semarang Regency. A quantitative explanatory research design was employed using data collected from 70 MSME owners selected through purposive sampling. Primary data were obtained through an online questionnaire and analyzed using multiple linear regression with SPSS. The findings indicate that price penetration, product innovation, and competitor orientation have positive and significant effects on marketing performance. In contrast, digital marketing does not have a significant direct effect on marketing performance. Simultaneously, however, digital marketing, price penetration, product innovation, and competitor orientation collectively exert a positive and significant influence on marketing performance. These findings suggest that competitive pricing strategies, continuous product innovation, and market-oriented competitive capabilities are more influential than digital marketing alone in enhancing MSME marketing performance. This study contributes to the strategic marketing literature by providing empirical evidence from the MSME sector in an emerging economy and offers practical implications for policymakers and business practitioners to strengthen MSME competitiveness through innovation support, digital capability development, and market-oriented business strategies. Keywords: Digital Marketing; Price Penetration; Product Innovation; Competitor Orientation; Marketing Performance